Easy Information about research: getting the message out to people with learning disabilities. (June 2015) - Goodwin, Julian; Mason, Victoria; Williams, Val; Townsley, Ruth; Williams, Val; Tarleton, Beth
<x xml:space="preserve">Abstract</x> Accessible Summary People with learning disabilities have a right to be given easy information about research which is about their lives. At the Norah Fry Research Centre, we have tried to do that. We have employed a person with learning disabilities Julian Goodwin. In this paper, he looks back at the importance of the work he has done. We think about the questions and difficulties in making information about research 'easy'. For instance different people with learning disabilities need different types of information. Easy information is changing, and we need to look forward to better ways of getting research messages out to people with learning disabilities. Summary This paper discusses the provision of easy information about research to people with learning disabilities, their families and supporters. We explore some different ways we have used over the past 25 years, to make sure that research has the greatest impact both in the UK and abroad. We discuss first the process of providing easy‐read versions of research at the Norah Fry Research Centre, where two of us, Goodwin and Townsley, worked on a series called Plain Facts funded by the Joseph Rowntree Foundation. We have always used different media such as audio, but more recently, have started to use video as a way of getting information out to people with learning disabilities. We aim to present the 'easy information' work done at Norah Fry, to reflect on its impact, and set it within the context of the move towards accessible information more generally, questioning some of the premises about 'impact' on which accessible information is based.